HCI in mobility, transport, and automotive systems : First International Conference, MobiTAS 2019, held as part of the 21st HCI International Conference, HCII 2019, Orando, FL, USA, July 26-31, 2019, proceedings /: First International Conference, MobiTAS 2019, held as part of the 21st HCI International Conference, HCII 2019, Orando, FL, USA, July 26-31, 2019, proceedings. ([2019]) - Unknown
No abstract available